Tantangan Dan Peluang Credit Union Sebagai Penguat Ketahanan Masyarakat - Binawan, Alexius Andang; Masiun, Stefanus (Jurnal Kajian Stratejik Ketahanan Nasional, 2024)
This article will explain the dynamics of the role of credit unions (CU) in community empowerment in the context of social resilience. Keling Kumang Credit Union in West Kalimantan was used as a case study to see the empowerment efforts carried out, because CU places greater emphasis on human empowerment. Empowerment or financial literacy is just a means. Through qualitative research based on analysis of social media and documents, the social role of CUs will be examined. By using the observations of Peter Davis as a cooperative 'guru', the challenges and opportunities of a credit union are also explained. Peter Davis' reflection points will be applied in the context of CUs in West Kalimantan in general and for CU Keling Kumang in particular. With the SWOT method, namely looking at strengths, weaknesses, opportunities and challenges, several reflective conclusions will be drawn. Apart from that, proposals and suggestions were submitted, so that in the future CU can continue to play a role in accordance with its mission, namely building community welfare in a broad sense.